2016
DOI: 10.5301/heartint.5000230
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Management in Older Heart Failure Patients: A Complex Clinical Problem

Abstract: BackgroundAtrial fibrillation (AF) and heart failure (HF), two problems of growing prevalence as a consequence of the ageing population, are associated with high morbidity, mortality, and healthcare costs. AF and HF also share common risk factors and pathophysiologic processes such as hypertension, diabetes mellitus, ischemic heart disease, and valvular heart disease often occur together. Although elderly patients with both HF and AF are affected by worse symptoms and poorer prognosis, there is a paucity of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“… 5 A possible explanation may be that incident AF beyond 1 year is a marker of HF progression and/or frailty in HF. 7 , 21 Our sex-specific analysis revealed that incident AF was associated with a greater loss in expected lifetime among women than men. 22 AF is associated with higher mortality among women in the non-HF setting, and our data support recent work that shows higher mortality among women in an HF-setting.…”
Section: Discussionmentioning
confidence: 75%
“… 5 A possible explanation may be that incident AF beyond 1 year is a marker of HF progression and/or frailty in HF. 7 , 21 Our sex-specific analysis revealed that incident AF was associated with a greater loss in expected lifetime among women than men. 22 AF is associated with higher mortality among women in the non-HF setting, and our data support recent work that shows higher mortality among women in an HF-setting.…”
Section: Discussionmentioning
confidence: 75%
“…Compared to coronary artery disease and stroke, the differences between women and men with HF and/or AF have received less attention [ 36 ]. AF often occurs as a cause or consequence of HF [ 15 , 16 ]. Adverse outcomes are worse when AF and HF coexist [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AF prevalence also steeply increases with age [ 14 ]. Multiple relationships can exist between HF and AF, including shared risk factors and the causation of one by the other [ 14 , 15 ]. Recently, two meta-analyses have reported that the coexistence of AF in HF patients increased the odds of mortality from 14% to 57% when compared to HF alone [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used G*power 3.1 to calculate the adequate sample size for this study (Faul et al, 2009 ). It was determined that the sample size of 170 patients was adequate for two‐tailed logistic regression analysis with an alpha level of 0.05, power of 90% and 1.9 odds ratio (OR) based on previous study (Pulignano et al, 2016 ); therefore, the sample size of 176 patients was sufficient.…”
Section: Methodsmentioning
confidence: 99%